Roll-type membrane grid material as well as preparation method and application thereof
By forming a fibrous membrane on a support grid and introducing carboxyl functional groups, a spiral wound membrane grid material with high porosity and high desalination rate is prepared, which solves the problem of insufficient porosity and desalination rate in the prior art and is suitable for separation, filtration and catalysis.
Patent Information
- Application Number
- CN202511493595.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-20
- Publication Date
- 2026-01-23
AI Technical Summary
There is room for improvement in the porosity and desalination rate of existing spiral wound membrane grid materials, and the bonding method between the supporting grid and the membrane needs to be improved to enhance performance.
A spiral wound membrane grid material with high porosity and high desalination rate was prepared by forming a fibrous membrane on a supporting grid through emulsion electrospinning, introducing carboxyl functional groups through modification liquid treatment, and combining it with alternating layers of porous grids and hot pressing.
It achieves high porosity and good desalination rate, and is suitable for separation, filtration and catalysis. The supporting grid and membrane are stably bonded.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of water treatment membrane technology, specifically relating to a spiral wound membrane grid material, its preparation method, and its application. Background Technology
[0002] Water pollution control and water environment management standards for discharge and reuse are becoming increasingly stringent. Membrane filtration technology, with its stability, high efficiency, and environmental friendliness, has gradually become a research and application hotspot in the water treatment field. Membrane filtration technology is widely used in various fields of wastewater treatment and reclaimed water. Spiral wound membrane modules have attracted much attention due to their high packing density, small footprint, and ease of maintenance. Spiral wound membrane modules typically consist of an inlet screen, membrane sheets on both sides, an outlet screen, and a collection pipe. The membrane sheets and screens on both sides are sequentially stacked to form a specific spiral wound structure. Due to its compact structure, spiral wound membrane modules have a relatively small footprint, which facilitates efficient water treatment within limited space.
[0003] Chinese patent (publication number CN118558158A) discloses a spiral wound hollow fiber membrane module and a method for preparing hollow fiber composite membrane filaments. The invention first prepares hollow fiber composite membrane filaments through phase transformation and interfacial polymerization processes. The membrane filaments are then specially designed to form a hollow fiber membrane sheet with one end closed and the other end open. One end of the membrane sheet is connected to a central tube, and a grid of the same size is used. Polyurethane is applied around the central tube, and finally a water-stop ring and a sealing ring are installed to form a spiral wound hollow fiber membrane module, which is then applied to the field of water treatment technology.
[0004] For spiral wound membrane grid materials, how to modify the surface of polymer fiber membranes to enhance their performance, and at the same time find new ways to combine them with the supporting grid to effectively improve porosity and obtain good desalination rate, has become a direction that needs to be studied. Summary of the Invention
[0005] To address the shortcomings of existing technologies, the present invention aims to provide a spiral wound membrane grid material, its preparation method, and its applications. The present invention obtains a multilayer functional fiber membrane through emulsion electrospinning and combines it with a support grid coated with glutaraldehyde. The spiral wound design achieves a high specific surface area and a compact structure. This spiral wound membrane grid material has high porosity and good desalination rate, and can be applied to fields such as separation, filtration, or catalysis.
[0006] The technical solution adopted by the present invention to solve the above-mentioned technical problems is as follows: In a first aspect, the present invention provides a method for preparing a spiral wound membrane grid material, comprising the following steps: S1. Dissolve cellulose triacetate in a solvent to form a cellulose triacetate solution, dissolve polyethylene glycol in deionized water to form a polyethylene glycol solution, mix the cellulose triacetate solution and the polyethylene glycol solution, add an emulsifier for emulsification treatment to obtain an emulsion, electrospin the emulsion onto a support grid to form a fiber membrane, and obtain a composite membrane after vacuum drying; S2. The composite membrane is first washed with deionized water, and then immersed in the modification solution for post-treatment to obtain a porous composite membrane. S3. The porous composite membrane and the porous grid are alternately stacked and hot-pressed together, and then wound into shape to obtain a spiral membrane grid material.
[0007] This invention uses a cellulose triacetate solution as the oil phase and a polyethylene glycol solution as the aqueous phase. After adding an emulsifier, an emulsion is obtained through high-speed homogenization and then electrospinned. A support grid is used as a receiving device to form a fiber membrane on the support grid. After soaking in a modified solution, a porous composite membrane is obtained. The membrane is then wound around a central tube to obtain a spiral wound membrane grid material.
[0008] As a preferred embodiment of the present invention, the porous mesh is made of polypropylene (PP). The properties of polypropylene itself determine its characteristics as a porous mesh: it possesses excellent chemical stability—resistance to acids, alkalis, and solvent corrosion—making it suitable for harsh environments such as chemical and environmental protection industries; it has low density and light weight, resulting in a very lightweight porous mesh that is easy to transport and install; it has good mechanical properties—sufficient rigidity, strength, and fatigue resistance, capable of withstanding certain loads and repeated stresses; it is non-toxic, easy to process and mold, and hydrophobic. The parameters of the polypropylene porous mesh can be selected as follows: thickness of 28~34 mil, angle of 90~105°, number of ribs (strips) of 9~12 per inch and / or width of 1000-1050 mm.
[0009] As a preferred embodiment of the present invention, the porous grid may be at least one of the following: WF2809, WF3109, WF3112, or WF3409.
[0010] As a preferred technical solution of the present invention, the porous grid is not limited to the above-mentioned materials, and other commercially available porous grid materials can also be selected.
[0011] As a preferred technical solution of the present invention, the preparation steps of the triacetic acid cellulose solution include: mixing 70-80 parts by weight of dimethyl sulfoxide and 20-30 parts by weight of dichloromethane, and then adding 8-10 parts by weight of triacetic acid cellulose and stirring for 20-24 hours to obtain a triacetic acid cellulose solution.
[0012] As a preferred embodiment of the present invention, the dimethyl sulfoxide may be in the following weight proportions: 70 parts, 72 parts, 74 parts, 76 parts, 78 parts, or 80 parts.
[0013] As a preferred embodiment of the present invention, the dichloromethane may be in the following weight proportions: 20 parts, 22 parts, 24 parts, 26 parts, 28 parts, or 30 parts.
[0014] As a preferred embodiment of the present invention, the weight parts of the triacetic acid cellulose can be 8 parts, 8.5 parts, 9 parts, 9.5 parts, or 10 parts.
[0015] As a preferred technical solution of the present invention, the preparation steps of the polyethylene glycol solution include: adding 4-6 parts by weight of polyethylene glycol to 90-100 parts by weight of deionized water, stirring at room temperature for 30-40 minutes, then heating to 80-90°C and stirring for 120-140 minutes, and cooling to room temperature to obtain the polyethylene glycol solution.
[0016] As a preferred embodiment of the present invention, the polyethylene glycol may be in the following weight proportions: 4 parts, 4.5 parts, 5 parts, 5.5 parts, or 6 parts.
[0017] As a preferred embodiment of the present invention, the emulsifier is selected from one or more of Span 80, Span 60 or Span 20.
[0018] As a preferred embodiment of the present invention, the emulsification treatment conditions include: using a homogenizer to stir evenly, with a homogenization rate of 5000~6000 r / min and a homogenization time of 4~6 min.
[0019] As a preferred embodiment of the present invention, the conditions for electrospinning include: an ambient temperature of 26~30℃, a relative humidity of 40~50%, a spinning voltage of 20~22kV, a spinning speed of 0.6~0.8mL / h, and a receiving distance of 10~16cm.
[0020] This invention prepares a fiber membrane by emulsion electrospinning. The main nanofiber is triacetate cellulose fiber, while polyethylene glycol is randomly distributed on the surface or inside of the fiber. By washing with deionized water before post-treatment, the water-soluble polyethylene glycol is removed, thereby realizing a porous structure in the fiber membrane and effectively improving the porosity of the material.
[0021] As a preferred embodiment of the present invention, the supporting grid is made of polypropylene and coated with glutaraldehyde.
[0022] This invention uses a support grid as a receiving device and coats the support grid with a crosslinking agent, glutaraldehyde. A fiber membrane is formed on the glutaraldehyde-coated support grid by an emulsion electrospinning process. The glutaraldehyde and polyethylene glycol at the contact surface between the fiber membrane and the support grid can be crosslinked during vacuum drying, thereby ensuring the stable bonding between the fiber membrane and the support grid in the composite membrane.
[0023] As a preferred technical solution of the present invention, the vacuum drying conditions include: a vacuum degree of 0.04~0.08MPa, a temperature of 70~80℃, and a time of 8~10h.
[0024] As a preferred embodiment of the present invention, the preparation steps of the modified liquid include: adding 20-30 parts by weight of sodium hydroxide to 600-800 parts by weight of deionized water, then adding 0.08-0.12 parts by weight of 2,2,6,6-tetramethylpiperidine-1-oxy radical, 1.8-2.4 parts by weight of sodium bromide and 4-8 parts by weight of sodium hypochlorite aqueous solution with a mass concentration of 6-14% and stirring evenly to obtain the modified liquid.
[0025] As a preferred technical solution of the present invention, the post-treatment conditions include: soaking in the modified solution for 40-50 hours, then adding anhydrous ethanol to terminate the reaction, washing with water, and drying in an oven at 60-70°C to obtain a porous composite membrane.
[0026] In this invention, the composite membrane is immersed in a modification solution. The sodium hydroxide aqueous solution in the modification solution can achieve alkaline hydrolysis of cellulose triacetate fibers, removing the acetyl groups of cellulose triacetate. Then, an oxidation system of 2,2,6,6-tetramethylpiperidine-1-oxy radical / sodium hypochlorite / sodium bromide is used to oxidize the hydroxyl groups on the cellulose to carboxyl groups, thereby introducing carboxyl functional groups, improving the retention rate of metal cations, and thus improving the desalination rate of the material.
[0027] A second aspect of the present invention provides a spiral wound membrane grid material prepared by the method described in the first aspect.
[0028] A third aspect of the present invention provides an application of a spiral wound membrane grid material prepared by the method described in the first aspect in the fields of separation, filtration, or catalysis.
[0029] Compared with the prior art, the present invention has the following beneficial effects: (1) In this invention, a triacetic acid cellulose solution is used as the oil phase and a polyethylene glycol solution is used as the aqueous phase. After adding an emulsifier, an emulsion is obtained by high-speed homogenization and the emulsion is electrospun. A support grid is used as a receiving device to form a fiber membrane on the support grid. After soaking in a modified liquid, a porous composite membrane is obtained and then wound around a central tube to obtain a spiral wound membrane grid material.
[0030] (2) The present invention prepares a fiber membrane by emulsion electrospinning. The main body of the nanofiber is triacetic acid cellulose fiber, and polyethylene glycol is randomly distributed on the surface or inside of the fiber. By washing with deionized water before post-treatment, the water-soluble polyethylene glycol is removed, thereby realizing a porous structure in the fiber membrane and effectively improving the porosity of the material.
[0031] (3) In this invention, the composite membrane is immersed in a modification solution. The sodium hydroxide aqueous solution in the modification solution can achieve alkaline hydrolysis of cellulose triacetate, remove the acetyl groups of cellulose triacetate, and then use the oxidation system of 2,2,6,6-tetramethylpiperidine-1-oxy free radical / sodium hypochlorite / sodium bromide to oxidize the hydroxyl groups on the cellulose to carboxyl groups, thereby introducing carboxyl functional groups, improving the retention rate of metal cations, and thus improving the desalination rate of the material.
[0032] (4) The present invention uses a support grid as a receiving device and coats the support grid with a crosslinking agent glutaraldehyde. A fiber membrane is formed on the support grid coated with glutaraldehyde by an emulsion electrospinning process. The glutaraldehyde and polyethylene glycol at the contact surface between the fiber membrane and the support grid can be crosslinked during the vacuum drying process, thereby ensuring the stable bonding between the fiber membrane and the support grid in the composite membrane. Detailed Implementation
[0033] To facilitate understanding of the present invention, the following embodiments are provided. Those skilled in the art should understand that these embodiments are merely illustrative and should not be construed as limiting the scope of the invention.
[0034] The sources of some components in the examples and comparative examples are as follows: Cellulose triacetate, item number C195717, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; polyethylene glycol, item number P103728, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; 2,2,6,6-tetramethylpiperidine-1-oxygen radical (TEMPO), item number T106827, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; sodium bromide, CAS number 7647-15-6, was purchased from Shanghai Maclean Biochemical Technology Co., Ltd.; sodium hypochlorite aqueous solution, item number S101636, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0035] Example 1 This embodiment provides a method for preparing a spiral wound membrane grid material, including the following steps: S1. By weight, mix 80 parts of dimethyl sulfoxide and 20 parts of dichloromethane, then add 10 parts of cellulose triacetate and stir for 24 hours to obtain a cellulose triacetate solution; the preparation steps of the polyethylene glycol solution include: by weight, add 6 parts of polyethylene glycol to 100 parts of deionized water, stir at room temperature for 40 minutes, then heat to 90°C and stir for 120 minutes, cool to room temperature to obtain a polyethylene glycol solution; mix 100 parts of the cellulose triacetate solution with 20 parts of the polyethylene glycol solution, and add... 0.8 parts of emulsifier Span 80 were emulsified using a homogenizer (homogenization rate 6000 r / min, homogenization time 4 min) to obtain an emulsion. The emulsion was then electrospun (ambient temperature 30℃, relative humidity 40%, spinning voltage 22kV, spinning speed 0.8 mL / h, receiving distance 16 cm) to form a fiber membrane on a polypropylene support grid coated with glutaraldehyde. After vacuum drying (vacuum degree 0.08 MPa, temperature 80℃, time 8 h), a composite membrane was obtained. S2. The composite membrane is first washed with deionized water, then soaked in the modification solution for 50 hours, and then anhydrous ethanol is added to terminate the reaction. After washing with water, it is dried in an oven at 70°C to obtain a porous composite membrane. S3. The porous composite membrane and the porous grid (model WF2809, material PP, thickness 28mil, diameter (rib) number 9 / inch) are alternately stacked and hot-pressed together, and then wound into shape to obtain the roll-up membrane grid material.
[0036] The preparation steps of the modified solution include: adding 30 parts by weight of sodium hydroxide to 800 parts by weight of deionized water, then adding 0.12 parts by weight of 2,2,6,6-tetramethylpiperidine-1-oxy radical, 2.4 parts by weight of sodium bromide and 8 parts by weight of 6% sodium hypochlorite aqueous solution and stirring evenly to obtain the modified solution.
[0037] Example 2 This embodiment provides a method for preparing a spiral wound membrane grid material, including the following steps: S1. By weight, 70 parts of dimethyl sulfoxide and 30 parts of dichloromethane are mixed, and then 8 parts of cellulose triacetate are added and stirred for 20 hours to obtain a cellulose triacetate solution; the preparation steps of the polyethylene glycol solution include: by weight, 4 parts of polyethylene glycol are added to 90 parts of deionized water, stirred at room temperature for 30 minutes, then heated to 80°C and stirred for 140 minutes, and cooled to room temperature to obtain a polyethylene glycol solution; 80 parts of the cellulose triacetate solution are mixed with 10 parts of the polyethylene glycol solution, and 0. Four parts of emulsifier Span 60 were emulsified using a homogenizer (homogenization rate 5000 r / min, homogenization time 6 min) to obtain an emulsion. The emulsion was then electrospun (ambient temperature 26℃, relative humidity 50%, spinning voltage 20kV, spinning speed 0.6mL / h, receiving distance 10cm) to form a fiber membrane on a polypropylene support grid coated with glutaraldehyde. After vacuum drying (vacuum degree 0.04MPa, temperature 70℃, time 10h), a composite membrane was obtained. S2. The composite membrane is first washed with deionized water, then soaked in the modified solution for 40 hours, then anhydrous ethanol is added to terminate the reaction, washed with water, and dried in an oven at 60°C to obtain a porous composite membrane. S3. The porous composite membrane and the porous grid (model WF3112, material PP, thickness 31mil, diameter (rib) number 12 / inch) are alternately stacked and hot-pressed together, and then wound into shape to obtain the roll-up membrane grid material.
[0038] The preparation steps of the modified solution include: adding 20 parts by weight of sodium hydroxide to 600 parts by weight of deionized water, then adding 0.08 parts by weight of 2,2,6,6-tetramethylpiperidine-1-oxy radical, 1.8 parts by weight of sodium bromide and 4 parts by weight of sodium hypochlorite aqueous solution with a mass concentration of 14% and stirring evenly to obtain the modified solution.
[0039] Example 3 This embodiment provides a method for preparing a spiral wound membrane grid material, including the following steps: S1. By weight, mix 75 parts dimethyl sulfoxide and 25 parts dichloromethane, then add 9 parts triacetate cellulose and stir for 22 hours to obtain a triacetate cellulose solution; the preparation steps of the polyethylene glycol solution include: by weight, add 5 parts polyethylene glycol to 95 parts deionized water, stir at room temperature for 35 minutes, then heat to 85℃ and stir for 130 minutes, cool to room temperature to obtain a polyethylene glycol solution; mix 90 parts triacetate cellulose solution with 15 parts polyethylene glycol solution, and add 0 6 parts of emulsifier Span 20 were emulsified using a homogenizer (homogenization rate 5500 r / min, homogenization time 5 min) to obtain an emulsion. The emulsion was then electrospun (ambient temperature 28℃, relative humidity 45%, spinning voltage 21kV, spinning speed 0.7 mL / h, receiving distance 13 cm) to form a fiber membrane on a polypropylene support grid coated with glutaraldehyde. After vacuum drying (vacuum degree 0.06 MPa, temperature 75℃, time 9 h), a composite membrane was obtained. S2. The composite membrane is first washed with deionized water, then soaked in the modified solution for 45 hours, and then anhydrous ethanol is added to terminate the reaction. After washing with water, it is dried in an oven at 65°C to obtain a porous composite membrane. S3. The porous composite membrane and the porous grid (model WF3409, material PP, thickness 34mil, diameter (rib) number 9 / inch) are alternately stacked and hot-pressed together, and then wound into shape to obtain the roll-type membrane grid material.
[0040] The preparation steps of the modified solution include: adding 25 parts by weight of sodium hydroxide to 700 parts by weight of deionized water, then adding 0.10 parts by weight of 2,2,6,6-tetramethylpiperidine-1-oxy radical, 2.2 parts by weight of sodium bromide and 6 parts by weight of sodium hypochlorite aqueous solution with a mass concentration of 8% and stirring evenly to obtain the modified solution.
[0041] Comparative Example 1 The difference between this comparative example and Example 1 is that the surface of the polypropylene support grid is not coated with glutaraldehyde.
[0042] Comparative Example 2 The difference between this comparative example and Example 1 is that in step S2, the sample is not immersed in the modified solution for post-treatment.
[0043] Comparative Example 3 The difference between this comparative example and Example 1 is that deionized water washing is not performed before post-treatment in step S2.
[0044] Comparative Example 4 The difference between this comparative example and Example 1 is that sodium hydroxide is not added to the modified solution.
[0045] Comparative Example 5 The difference between this comparative example and Example 1 is that no 2,2,6,6-tetramethylpiperidine-1-oxy radical is added to the modified solution.
[0046] The performance of the porous composite membranes of the above embodiments and comparative examples was tested using the following methods: Porosity testing: The test shall be conducted in accordance with the requirements of GB / T 42697-2023 Test Method for Porosity of Nonwoven Fabrics.
[0047] Desalination rate test: The test shall be conducted in accordance with the requirements of GB / T 32373-2015 Reverse osmosis membrane test method.
[0048] The performance test data above are shown in Table 1.
[0049] Table 1 Performance Test Results
[0050] As can be seen from the above, the present invention uses a cellulose triacetate solution as the oil phase and a polyethylene glycol solution as the aqueous phase. After adding an emulsifier, an emulsion is obtained by high-speed homogenization and then electrospinning of the emulsion. A support grid is used as a receiving device to form a fiber membrane on the support grid. After soaking in a modified liquid, a porous composite membrane is obtained. The membrane is alternately stacked with the porous grid and hot-pressed together, and then wound to form a spiral wound membrane grid material.
[0051] Compared to Example 1, the polypropylene support grid surface was not coated with glutaraldehyde, and the polypropylene support grid and fiber membrane in the composite membrane would separate during immersion, thus the product could not be formed (Comparative Example 1); compared to Example 1, in step S2, no immersion in the modification solution was performed for post-treatment, and no carboxyl functional groups were introduced, resulting in a decrease in desalination rate (Comparative Example 2); compared to Example 1, in step S2, no deionized water washing was performed before post-treatment, resulting in incomplete formation of the porous structure and poor oxidation effect of the oxidation system, thus reducing porosity and desalination rate (Comparative Example 3); compared to Example 1, no sodium hydroxide was added to the modification solution, making it difficult for triacetate cellulose fibers to undergo alkaline hydrolysis and remove acetyl groups, thus reducing desalination rate (Comparative Example 4); compared to Example 1, no 2,2,6,6-tetramethylpiperidine-1-oxy radical was added to the modification solution, resulting in poor oxidation effect of the oxidation system and a decrease in desalination rate (Comparative Example 5).
Claims
1. A method for preparing a spiral wound membrane grid material, characterized in that, Includes the following steps: S1. Dissolve cellulose triacetate in a solvent to form a cellulose triacetate solution, dissolve polyethylene glycol in deionized water to form a polyethylene glycol solution, mix the cellulose triacetate solution and the polyethylene glycol solution, add an emulsifier for emulsification treatment to obtain an emulsion, electrospin the emulsion onto a support grid to form a fiber membrane, and obtain a composite membrane after vacuum drying; S2. The composite membrane is first washed with deionized water, and then immersed in the modification solution for post-treatment to obtain a porous composite membrane. S3. The porous composite membrane and the porous grid are alternately stacked and hot-pressed together, and then wound into shape to obtain a spiral membrane grid material.
2. The method for preparing a spiral wound membrane grid material according to claim 1, characterized in that, The preparation steps of the cellulose triacetate solution include: mixing 70-80 parts by weight of dimethyl sulfoxide and 20-30 parts by weight of dichloromethane, then adding 8-10 parts by weight of cellulose triacetate and stirring for 20-24 hours to obtain the cellulose triacetate solution.
3. The method for preparing a spiral wound membrane grid material according to claim 1, characterized in that, The preparation steps of the polyethylene glycol solution include: adding 4-6 parts by weight of polyethylene glycol to 90-100 parts by weight of deionized water, stirring at room temperature for 30-40 minutes, then heating to 80-90°C and stirring for 120-140 minutes, and cooling to room temperature to obtain the polyethylene glycol solution.
4. The method for preparing a spiral wound membrane grid material according to claim 1, characterized in that, The emulsifier is selected from one or more of Span 80, Span 60 or Span 20.
5. The method for preparing a spiral wound membrane grid material according to claim 1, characterized in that, The conditions for electrospinning include: ambient temperature of 26~30℃, relative humidity of 40~50%, spinning voltage of 20~22kV, spinning speed of 0.6~0.8mL / h, and receiving distance of 10~16cm.
6. The method for preparing a spiral wound membrane grid material according to claim 1, characterized in that, The supporting grid is made of polypropylene and coated with glutaraldehyde.
7. The method for preparing a spiral wound membrane grid material according to claim 1, characterized in that, The preparation steps of the modified solution include: adding 20-30 parts by weight of sodium hydroxide to 600-800 parts by weight of deionized water, then adding 0.08-0.12 parts by weight of 2,2,6,6-tetramethylpiperidine-1-oxy radical, 1.8-2.4 parts by weight of sodium bromide and 4-8 parts by weight of sodium hypochlorite aqueous solution with a mass concentration of 6-14% and stirring evenly to obtain the modified solution.
8. The method for preparing a spiral wound membrane grid material according to claim 1, characterized in that, The post-treatment conditions include: soaking in the modified solution for 40-50 hours, adding anhydrous ethanol to terminate the reaction, washing with water, and drying in an oven at 60-70°C to obtain a porous composite membrane.
9. A type of rolled membrane grid material, characterized in that, Obtained by the preparation method described in any one of claims 1 to 8.
10. The application of the spiral wound membrane grid material obtained by the preparation method according to any one of claims 1 to 8 in the fields of separation, filtration or catalysis.
Citation Information
Patent Citations
Roll-type hollow fiber membrane module and preparation method thereof as well as hollow fiber composite membrane silk
CN118558158A